Currency Risk Management Practices of Indian Export SMEs: A Descriptive Study - Vasumathy, S. (Indian Journal of Finance, 2015)
The existing literature is abundant with studies done to understand the risk management practices of multinationals and big business houses. The objectives with which these studies are conducted include understanding the practices, analyzing the hedging techniques adopted, examining the attitude of the firms towards derivative usage, and so forth. Since there is a dearth of studies conducted on the Indian small and medium sector, this study attempted to describe the risk management practices of Indian small and medium enterprises. A descriptive approach was adopted for getting a deeper insight into the practices. The results indicated extensive usage of forward contracts, existence of risk management systems in some firms, and comparatively less awareness about derivatives among the firms. The study found that the attitude of the firms towards usage of derivatives and employing a formal risk management system to monitor exchange rates was neutral as they perceived that these were meant only for multinationals. The study recommended increasing the awareness of derivatives among the firms as the firms did not have the means to adopt alternate techniques like natural and operational hedges. It also insisted that the firms should monitor exchange rates on a regular basis in the forthcoming years as the economic policies are edging towards stabilizing the economy.